Triple-Q state in magnetic breathing kagome lattice - Hangyu Zhou; Manuel dos Santos Dias; Shijian Bao; Hanchen Lu; Youguang Zhang; Weisheng Zhao; Samir Lounis (npj Spintronics)
Abstract Magnetic frustration in two-dimensional spin lattices with triangular motifs underpins a series of exotic states, ranging from multi-Q configurations to disordered spin glasses. The antiferromagnetic kagome lattice, characterized by its network of corner-sharing triangles, represents a paradigmatic frustrated system exhibiting macroscopic degeneracy. Expanding upon the kagomerization mechanism, we focus on the magnetic breathing kagome lattice formed by an Mn monolayer deposited on a heavy metal substrate and capped with h-BN. The Mn kagome arrangement induces pronounced magnetic frustration, as evidenced by the nearly flat bands derived from spin spiral energy calculations. Including further-neighbor interactions reveals a spin spiral energy minimum along the Γ-K line and an intriguing triple-Q state with nonzero topological charge, potentially leading to highly nonlinear Hall effects. Furthermore, the flat band properties can further give rise to an even more complex spin configuration, marked by several Q-pockets in the spin structure factor. These results present a fertile ground for advancing the study of multi-Q states and exploring emergent topological phenomena.